Creative industries curriculum design for living and leading amid uncertainty. (2nd January 2022) - Crimmins, Gail; Lipton, Briony; McIntyre, Joanna; de Villiers Scheepers, Margarietha; English, Peter
ABSTRACT: Government policies are forcing universities to narrowly emphasise employability, which does not bode well for the Creative Industries (CI). Despite being one of the fastest-growing and diverse employment sectors, CI degrees have been criticised for failing to deliver adequate employment prospects. The employability focus, which serves 'the [economic] system' [Habermas, Jürgen. 1987. The Theory of Communicative Action. Volume 2 Lifeworld and Ssystem: The Ccritique of Functionalist reason, Translated by T McCarthy. Cambridge: Polity Press], ignores both the employment precarity in the sector and diminishes universities' capacity to serve the lifeworld (Harbernas) to facilitate graduate citizenship. Dichotomising employability and citizenship fail to consider the supercomplexity of the twenty-first Century [Barnett, Ronald. 2000a. Realizing the University in an Age of Supercomplexity . Buckingham: Open University Press], constituted by the co-existence of a multiplicity of epistemological frameworks. In this paper, we draw on supercomplexity and the concept of the system and lifeworld to investigate how to develop CI curricula that foster employability and citizenship. Using an illustrative case, we demonstrate how CI curricula can be designed to support students to navigate multiple ideological geographies, facilitate employability, and contribute to civic society.